Isolation and Screening of Antibiotics Producing Streptomyces spp from the Soil Collected around the Root of Alnus nepalensis from Godawari - Baniya, Amina; Singh, Sushma; Singh, Minu; Nepal, Pragya; Adhikari, Mahesh; Aryal, Sagar; Adhikari, Anurag (Nepal Journal of Biotechnology, 2019)
Actinomycetes are considered as the most invaluable prokaryotes whose genome mining show a great number of putative secondary metabolite biosynthesis pathways as well as gene clusters ranging from 20 to 50 per genome. The genus Streptomyces has been explored for its ability to produce 60% antibiotics worldwide. Alnus nepalensis (Alder) has been found to harbor diverse Eubacteria in its rhizosphere. To evaluate the antibiotic production potential from Actinomycetes, we collected soil samples from rhizosphere (5-7 cm deep) of Alder tree. Primary screening was done by cross-streak method against Multidrug Resistant (MDR) such as Methicillin resistant Staphylococcus auereus (MRSA), Vancomycin resistant Enterococcus feacalis (VRE), Imepenem resistant Acinetobacterbaumannii, Vancomycin resistant Klebsiella pneumonia and Imepenem resistant E. coli as well as Non-MDRs (E. coli, Bacillus subtilis, Klebsiella pneumoniae, S. aeureu and Enterococcus feacalis). Extraction of antibiotics was done using rota-vapour from extract obtained by solid-substrate fermentation technique followed by solvent extraction. Secondary screening was done using well diffusion assay against MDRs. Among total of 40 isolates of Actinomycetes recovered, 14 showed remarkable zone of inhibition (ZOI) to various MDRs. NASA 303 showed 26 mm of ZOI against VRE, NASA 101 had ZOI of 34 mm against MRSA, NASA 319 had 33.7 mm ZOI against Imepenem resistant E. coli, NASA 306 had 36 mm of ZOI against Vancomycin resistant Klebsiella pneumoniae, and NASA 108 showed ZOI of 29.6 mm against Imepenem resistant E. faecalis. This investigation revealed that the Actinomycetes found in Rhizosphere of Alder tree had MDR killing potent antibiotics, which needs to be further explored.